2018
DOI: 10.1002/2017je005270
|View full text |Cite
|
Sign up to set email alerts
|

Wind‐Eroded Crater Floors and Intercrater Plains, Terra Sabaea, Mars

Abstract: Ancient impact craters with wind‐eroded layering on their floors provide a record of resurfacing materials and processes on early Mars. In a 54 km Noachian crater in Terra Sabaea (20.2°S, 42.6°E), eolian deflation of a friable, dark‐toned layer up to tens of meters thick has exposed more resistant, underlying light‐toned material. These layers differ significantly from strata of similar tone described in other regions of Mars. The light‐toned material has no apparent internal stratification, and visible/near‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 113 publications
(170 reference statements)
1
21
0
Order By: Relevance
“…The morphology and geographic extent of the interpreted paleo‐dune field indicates that paleo‐sediment‐transport direction was from the southeast, perhaps sourced from eroding highlands in Terra Sabaea (Irwin et al, ). Southeast to northwest sediment transport follows the continental‐scale topographic gradient from highland toward lowland terrain on modern Mars, and the dune strata in this area may preserve evidence of an aeolian transport corridor that brought sediment to the northern lowlands.…”
Section: Discussionmentioning
confidence: 99%
“…The morphology and geographic extent of the interpreted paleo‐dune field indicates that paleo‐sediment‐transport direction was from the southeast, perhaps sourced from eroding highlands in Terra Sabaea (Irwin et al, ). Southeast to northwest sediment transport follows the continental‐scale topographic gradient from highland toward lowland terrain on modern Mars, and the dune strata in this area may preserve evidence of an aeolian transport corridor that brought sediment to the northern lowlands.…”
Section: Discussionmentioning
confidence: 99%
“…Surrounding materials have a relatively uniform composition and likely represent a mixture of impact ejecta, regolith and other unconsolidated materials (Tanaka et al, 1988). Bedrock plains are spectrally diverse and commonly contain multiple spectrally and morphologically distinctive subunits (Edwards et al, 2014;Irwin et al, 2018;Rogers et al, 2009;Wray et al, 2013). Orbital thermal infrared (TIR) and visible/near-infrared (VNIR) spectroscopy indicates many bedrock plain host olivine-enriched or olivine-and pyroxene-enriched surfaces (Edwards et al, 2014;Loizeau et al, 2012;Ody et al, 2013;Rogers & Fergason, 2011).…”
Section: Orbital Identification Of Bedrock and Previous Bedrock Mappimentioning
confidence: 99%
“…The spectral, morphological, and thermophysical properties of bedrock plains led to effusive volcanism and/or exposed mafic intrusions being favored as the petrogenic origin of bedrock materials (Edwards et al, ; Rogers & Nazarian, ). However, several newer observations suggest this interpretation is incorrect for many bedrock plains (Irwin et al, ; Rogers et al, ). A study of five heavily degraded Noachian‐aged craters hosting intracrater bedrock plains indicates that bedrock materials are friable, inconsistent with an effusive or intrusive igneous origin (Irwin et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Low-viscosity lava flows have resurfaced some crater floors (e.g., Gusev crater as described by Arvidson et al, 2006), but the extent of this flooding is debated on the basis of crater floor morphology and spectroscopy (e.g., Edwards et al, 2014;Irwin et al, 2018;Rogers et al, 2018). Carr (1981) observed that intercrater plains are "intrinsically difficult to interpret" because their surfaces have been reworked through time, removing most diagnostic landforms.…”
Section: Previous Workmentioning
confidence: 99%